Smart Energy Research : At the Crossroads of Engineering, Economics, and Computer Science : 3rd and 4th IFIP TC 12 International Conferences, SmartER Europe 2016 and 2017, Essen, Germany, February 16-18, 2016, and February 9, 2017, Revised Selected Papers /: At the Crossroads of Engineering, Economics, and Computer Science : 3rd and 4th IFIP TC 12 International Conferences, SmartER Europe 2016 and 2017, Essen, Germany, February 16-18, 2016, and February 9, 2017, Revised Selected Papers. (2017) - Unknown
No abstract available